The Unwelcome Soldier: How Post-War Experiences Shaped PTSD in Vietnam Veterans - Kleinsorge, Alex (Kansas State University. Dept. of History, 2011)
While the conflict in Southeast Asia ended with the withdrawal of American military forces from Saigon Vietnam on March 25, 1973, the war still raged for thousands of veterans. These veteran’s experiences in Vietnam took an emotional and psychological toll that was furthered by their often less-than-welcoming homecoming experiences. The frequency and severity of stress disorders, such as post-traumatic stress disorder (PTSD), were amplified among Vietnam veterans upon their homecoming due to the maltreatment by the public and mismanagement by the military.
Keywords: PTSD; Veteran experience